2023
DOI: 10.1108/itp-05-2022-0353
|View full text |Cite
|
Sign up to set email alerts
|

Abusive supervision and cyberloafing: an investigation based on Stressor-Emotion-CWB theory

Abstract: PurposeCyberloafing is an organization-directed counterproductive work behavior (CWB). One stream of literature deems cyberloafing to be bad for organizations and their employees, while another suggests cyberloafing is a coping response to stressful work events. Our work contributes to the latter stream of literature. The key objective of our study is to examine whether cyberloafing could be a means to cope with a stressful work event-abusive supervision, and if yes, what mediating and boundary conditions are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 154 publications
0
1
0
Order By: Relevance
“…Firstly, this study expands the related research (Andel et al, 2021;Batabyal & Bhal, 2020;Bhattacharjee & Sarkar, 2023;Chavan et al, 2021;Elciyar & Simsek, 2021;Hu et al, 2021;Peng et al, 2023) on the influencing factors of cyberloafing behaviour. Previous studies on antecedents of cyberloafing behaviour mainly focus on individual characteristics (Lim & Teo, 2005) and organisational circumstances (Lim, 2002;; limited studies concentrate on the impact of leadership on cyberloafing behaviour (Bhattacharjee & Sarkar, 2023;Lim et al, 2021;Peng et al, 2023;Zhang et al, 2022;Zoghbi Manrique de Lara & Viera-Armas, 2017). These studies found that authoritarian leadership and abusive supervision positively affect employees' cyberloafing, and ethical leadership and participative leadership negatively affect employees' cyberloafing.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Firstly, this study expands the related research (Andel et al, 2021;Batabyal & Bhal, 2020;Bhattacharjee & Sarkar, 2023;Chavan et al, 2021;Elciyar & Simsek, 2021;Hu et al, 2021;Peng et al, 2023) on the influencing factors of cyberloafing behaviour. Previous studies on antecedents of cyberloafing behaviour mainly focus on individual characteristics (Lim & Teo, 2005) and organisational circumstances (Lim, 2002;; limited studies concentrate on the impact of leadership on cyberloafing behaviour (Bhattacharjee & Sarkar, 2023;Lim et al, 2021;Peng et al, 2023;Zhang et al, 2022;Zoghbi Manrique de Lara & Viera-Armas, 2017). These studies found that authoritarian leadership and abusive supervision positively affect employees' cyberloafing, and ethical leadership and participative leadership negatively affect employees' cyberloafing.…”
Section: Introductionmentioning
confidence: 73%
“…Cyberloafing behaviour Lim (2002) developed the 11-item scale of cyberloafing and the mature scale has been validated by scholars (e.g. Bhattacharjee & Sarkar, 2023;Kim et al, 2016). We measured cyberloafing using Lim (2002)'s scale on a five-point Likert type scale (1 = never to 5 = always).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, previous work has focused on two approaches: (a) how negative leader behaviors increase employee cyberloafing (e.g. abusive supervision) (Agarwal and Avey, 2020; Bhattacharjee and Sarkar, n.d; Koay et al ., 2022; Lim et al ., 2021) and (b) how positive leader behaviors inhibit employee cyberloafing (e.g. ethical leadership and leader mindfulness) (Zoghbi-Manrique-de-Lara and Viera-Armas, 2017; Zoghbi-Manrique-de-Lara et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%